2020
DOI: 10.1097/icl.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Visual Rehabilitation With Contact Lenses Following Open Globe Trauma

Abstract: Objectives: To describe visual outcomes with various contact lens modalities in patients with a history of ocular trauma who underwent surgical open globe repair. Methods: Records of all patients with a history of open globe injury and repair at a tertiary care hospital between January 1, 2010, and December 31, 2016, were reviewed. Demographics, type of injury, and visual acuity were assessed before and after contact lens evaluation. Results: Of 214 patients who underwent open globe repair, 29 (13.6%) were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies have shown that a variety of contact lenses can be used effectively for visual rehabilitation after ocular trauma. 5 However, in China, most doctors and parents will not choose soft contact lenses for children, and scleral lenses are not approved for clinical use. Rigid gas-permeable keratocontact lenses are approved for clinical use in pediatric patients for the control of axial myopia, refractive correction of aphakic eyes after congenital cataract surgery, or other reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a variety of contact lenses can be used effectively for visual rehabilitation after ocular trauma. 5 However, in China, most doctors and parents will not choose soft contact lenses for children, and scleral lenses are not approved for clinical use. Rigid gas-permeable keratocontact lenses are approved for clinical use in pediatric patients for the control of axial myopia, refractive correction of aphakic eyes after congenital cataract surgery, or other reasons.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In the past few decades, visual rehabilitation of corneal scarring after corneal laceration has been treated by procedures such as corneal transplantation and contact lens correction. 3 5 Because of the good correction effects, rigid gas-permeable contact lenses (RGPCLs) are increasingly used for refractive correction after corneal trauma. 6 …”
mentioning
confidence: 99%
“…Most patients have an improvement in visual acuity following repair and management. [77][78][79] Final visual acuity after OGIs is better than 20/40 in up to 39% of patients, and only 9% of patients are likely to have no light perception. 74 Despite improvements in ocular surgery technique and technology, visual outcomes remain consistent with the OTS since its inception in 2002.…”
Section: Prognosismentioning
confidence: 99%
“…Representative techniques include anterior chamber IOL implantation, iris-fixed IOL implantation and trans-scleral fixed posterior chamber IOL implantation with or without suture [ 7 9 ]. The other approach is to apply contact lenses in a patient with aphakia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%